2019
DOI: 10.3389/fgene.2019.00804
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Apoptosis Gene Bcl-x Function Through Alternative Splicing

Abstract: Apoptosis plays a vital role in cell homeostasis during development and disease. Bcl-x, a member of the Bcl-2 family of proteins, is a mitochondrial transmembrane protein that functions to regulate the intrinsic apoptosis pathway. An alternative splicing (AS) event in exon 2 of Bcl-x results in two isoforms of Bcl-x with antagonistic effects on cell survival: Bcl-xL (long isoform), which is anti-apoptotic, and Bcl-xS (short isoform), which is pro-apoptotic. Bcl-xL is the most abundant Bcl-x protein and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 79 publications
0
80
0
2
Order By: Relevance
“…Its expression products together constitute the Bcl-2 family. Some members of the Bcl-2 family, such as Bcl-2, show resistance to apoptosis, whereas others, such as Bax, show promotion of apoptosis [71,72]. The results of this study indicated caspase-3 mediated apoptosis after GO exposure.…”
Section: Discussionmentioning
confidence: 53%
“…Its expression products together constitute the Bcl-2 family. Some members of the Bcl-2 family, such as Bcl-2, show resistance to apoptosis, whereas others, such as Bax, show promotion of apoptosis [71,72]. The results of this study indicated caspase-3 mediated apoptosis after GO exposure.…”
Section: Discussionmentioning
confidence: 53%
“…With decreased Bcl-2 and increased Bax and Bad, mitochondrion is stimulated to release cytochrome c, which in turn activates caspase-3, ultimately leading to apoptosis. 36 In this study, we revealed that after incubation with EVO, a dose-dependent increase of caspase-3, cleaved-caspase3, PARP and cleaved PARP was detected. Moreover, we observed downregulation of pro-apoptotic marker, Bax and Bad, and upregulation of antiapoptotic Bcl-2 proteins in EVO-treated osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 62%
“…intrinsic mitochondrial mediated apoptosis is considered to be the more critical way of the two (Stevens and Oltean 2019;Yoon et al 2020). Mitochondrial mediated apoptosis is largely regulated by the Bcl-2 protein family.…”
Section: Discussionmentioning
confidence: 99%